Konsep Kebebasan Beragama Dalam Islam: Analisis Pandangan Tāhir Ibn `Āsyūr - Muhammad Firdaus,; Misnawati, (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2024)
Religious freedom has been the subject of sustained debate among religious leaders throughout the history of human civilization. This has prompted various religious figures to develop and construct the concept with the aim of facilitating harmonious relations between religious communities. One of the figures who tried to elaborate on this concept was the prominent Muslim scholar, Tāhir Ibn Āshūr. This study examines the concept of religious freedom from Ibn Āshūr's perspective using a literature review or library study method. This article presents descriptive data, illustrating scholarly research with the potential to be further developed and applied in practice. The research approach used was descriptive qualitative, which aims to gather comprehensive information on the research topic. Data were collected through the systematic collation and categorization of online resources and related literature. The research found that Ibn Āshūr believed that religious freedom involves the inherent right of every individual to choose, believe, and practice their religion. Although convinced that Islam is the only true religion, he also showed respect for the beliefs and religions of others, demonstrating tolerance and recognition of the diversity of human beliefs. This article outlines three main aspects of Ibn Āshūr's views on religious freedom: the existence of restrictions on religious freedom, grounds in favor of religious conversion, and prohibition against free change of religion. This thorough analysis provides important insights into Ibn `Āshūr's views on religious freedom, and offers valuable implications for future research and practical applications.